VOLUNTARY HEALTH INSURANCE: FOREIGN EXPERIENCE FOR UKRAINE - Ivanchuk , O. (Pressing Problems of Public Administration, 2019)
In this research voluntary health insurance as a source of funding health care in different countries was investigated.Analysis of failures of voluntary health insurance market as a part of funding health care (adverse selection, risk selection, monopoly, moral hazard) was conducted. Advantages (mobilizing additional resources for health care, increased choice of health services for consumers, encouraging innovations) and potential risks (ensuring equitable financing and access to health care and efficiency of resource allocation) were determined.Types of voluntary health insurance in EU countries reviewed: 1) substitutive insurance covers that would otherwise be available from statutory health insurance scheme; 2) complementary insurance, cover for services excluded or not fully covered by the state; 3) supplementary insurance which offers increased consumer choice (more exhaustive insurance plans) and faster access to health services.It was concluded that the development of the voluntary health insurance market is influenced by several factors: positive demand (some people prefer not to risk); offer of services, for which people are ready to pay; technical capability to provide insurance services; levels of public expenditure on health care; the level of satisfaction regarding existing system among different population groups.Foreign experience indicates that depending on the specific role of voluntary health insurance in the founding health system, it could pose opportunities and risks for equitable progress towards universal health coverage.So, the private health insurance is incapable of encouraging solving social problems regarding health preservation and promotion of population without a proper regulation by state. Even in conditions of strict regulations, VHI is not an effective nor equitable method to to fund health care.